Chicken thigh microvascular training model improves resident surgical skills. Issue 6 (11th October 2017) - Creighton, Francis X.; Feng, Allen L.; Goyal, Neerav; Emerick, Kevin; Deschler, Daniel
Abstract : Objectives: Microsurgical techniques are essential for vessel anastomosis in free flap reconstructive surgery. However, teaching these skills intraoperatively is difficult. The chicken thigh microvascular model is a high‐fidelity model that has been previously validated to differentiate between skill levels of surgeons. This study aims to determine if this model objectively improves microsurgical skills. Study Design: Validation study Methods: Thirteen residents were given a tutorial on microvascular anastomosis and asked to perform anastomoses on the microvascular model. Anastomoses were video‐recorded and the time required for trainees to complete the first stitch of their first anastomosis was compared to the time required for the first stitch of their last anastomosis. Comparison of first and last stitch times was completed using a paired student t‐test. All participants completed a survey regarding their experience with the simulator. Results: There was a statistically significant decrease between the time required for the first stitch (235 s, 95%CI 198–272 s) compared to last stitch (120 s, 95%CI 92–149 s), and an average 48.7% (115 s) decrease in time ( p  < 0.001). Junior (PGY 2/3) and senior (PGY 4/5) residents had similar decreases in time, 49.1% and 48.21%, respectively. One hundred percent of residents felt they improved during the session and 92% of residents agreed or strongly agreed that their final stitch was better than their last stitch. All residents agreed or strongly agreed that the simulation is realistic, effective in teaching the procedure, and would translate to improved intraoperative performance. Conclusions: The chicken thigh model demonstrates objective improvements in resident microvascular surgical skills. Level of Evidence: NA